Evaluation of Wound Healing Activity of Mezhugu Kalimbu in Wistar Albino Rats - Faisal Atheefa; S.Ushakanthan (Journal of Ayurveda Campus, 2025)
Background: Chronic wounds continue to pose a serious healthcare challenge, and while Siddha medicine traditionally recommends Mezhugu Kalimbu for wound care, scientific validation of its healing properties is scarce. This study was designed to evaluate the wound-healing potential of Mezhugu Kalimbu and compare its efficacy with its individual components (Mezhugu and coconut oil), standard treatment (povidone iodine), and untreated control. Materials and Methods: Thirty Wistar albino rats were divided into five groups: untreated, standard (povidone iodine), coconut oil, Mezhugu, and Mezhugu Kalimbu. Full-thickness excision wounds were created, and topical applications were administered every 48 hours. Wound contraction rate and unit healing time were recorded and analyzed using SPSS. Results and Discussion: Mezhugu Kalimbu group showed significantly greater wound contraction compared to other groups (p < 0.05). Complete wound closure was achieved by Day 12, with a 100% mean contraction rate and the shortest mean healing time (8.32 days). The superior healing effect is attributed to the synergistic actions of Mezhugu with moistureretentive and antibacterial properties and coconut oil, which contributes anti-inflammatory and collagen-promoting effects. Conclusion: Mezhugu Kalimbu demonstrated significantly enhanced wound-healing activity compared to its individual components and the standard treatment, highlighting its potential as an effective, accessible, and affordable wound care formulation within Siddha medicine.